Reactions of organic nitriles with a three-coordinate molybdenum(III) complex and with a related molybdaziridine-hydride - Tsai, Yi-Chou; Stephens, Frances H.; Meyer, Karsten; Mendiratta, Arjun; Gheorghiu, Mircea D.; Cummins, Christopher C. (Organometallics, 2003)
Reactions of nitriles RCN with the sterically encumbered Mo(N[t-Bu]Ar) (1, Ar = 3,5-CHMe) or the somewhat less hindered Mo(H)(η-Me CNAr)(N[i-Pr]Ar) (2) have been investigated. Where R = Me or Ph, reaction with 1 results in reductive nitrile coupling and the formation of a diiminato product [u-NC(R)C(R)N][1]. In contrast, reaction of 1 with MeNCN surprisingly results in a stable, albeit highly congested, η adduct of the nitrile. When the less sterically hindered 2 is used, reaction with PhCN gives the diiminato product analogous to the one mentioned for the tert-butyl system, [u-NC(Ph)C(Ph)N] [Mo(N[i-Pr]Ar)], where molybdaziridine-hydride 2 has provided access to the three-coordinate Mo(N[i-Pr]Ar) (3) moiety. Use of a more bulky nitrile such as MesCN (Mes = 2,4,6-CH Me) results in formation of a bis-η compound, (η-MesCN)[3], Use of 9-anthracenylcarbonitrile results in head-to-tail C-C coupling of two monomers via the anthracenyl moiety. Detailed variable-temperature EPR and H NMR data are included for both molybdenum-containing starting materials and selected reaction intermediates and products. © 2003 American Chemical Society.